Static Analysis of Magnetic Field Affected Double Single Walled Carbon Nanotube System. (2016) - Agrawal, Swati; Gupta, V.K.; Kankar, P.K.
Abstract: In this study, a model to obtain the transverse displacement of double single walled carbon nanotube system (DSWNTS) with the application of longitudinal magnetic field has been developed. Here, two magnetically sensitive single walled carbon nanotubes are coupled by an elastic medium. The governing equation for transverse displacement of the system is modeled with the help of a modified couple stress theory. Total minimum potential energy principle is employed using variational formulation to develop the governing equations. This model is then applied to a cantilever beam problem and results are presented. Numerical results reveal that DSWNTS with larger length of CNTs would deflect more. Lesser deflection of DSWNTS is observed as the magnetic field increases. This system gives same transverse displacement for different values of size effect within the range of applied magnetic field. This mathematical model can be used for further dynamic analysis of other numerical or experimental models.